The Effect of Exposure to Carbon Monoxide (Co) Gas in Pregnant Women on The Incident of Weight Infants Born in Makassar City - Rapang, Arnita; Bara, Farida Tandi; Kusmiyati, Yuni; Supahar, Supahar; Nopiyanti, Nopiyanti (JURNAL INFO KESEHATAN, 2023)
Exposure to vehicle emissions, particularly carbon monoxide (CO), during pregnancy has been identified as a potential factor contributing to low birth weight in infants. CO's impact on the body involves binding with hemoglobin (Hb) in red blood cells, leading to placental dysfunction and alterations in oxygen flow efficiency to the uteroplacental. Such disruptions can adversely affect fetal growth. This study focuses on Makassar City, a rapidly developing urban area experiencing substantial growth in infrastructure and transportation. This research aims to assess the impact of carbon monoxide exposure on birth weight in pregnant women residing in Makassar City. The method of this study is a quantitative approach employing a descriptive cross-sectional design, which was adopted for this study. The research sample consisted of 120 pregnant women categorized based on their CO exposure levels—30 with low exposure, 60 with moderate exposure, and 30 with high exposure. Simple random sampling was utilized for participant selection. CO levels were measured using the Adalog 7000 multi-gas monitor. Data analysis included One Sample ANOVA and Linear Regression. The results show that data analysis indicated that pregnant women with low CO exposure had an average birth weight of 3110.83 grams. In contrast, those with moderate and high CO exposure exhibited average birth weights of 2840.33 grams and 2667.33 grams, respectively. The regression coefficient for CO exposure was -221,750, indicating that a 1 µm increase in carbon monoxide gas correlated with a decrease in birth weight by -221,750. The conclusion is that pregnant women who are exposed to high and moderate carbon monoxide gas during pregnancy had an effect on birth weight than mothers who are exposed to low carbon monoxide gas. Future research is needed to measure CO levels in the blood of pregnant women about birth weight.